Fulminant hepatic failure and serum phosphorus levels in children from the western part of Turkey - Yeşim ÖZTÜRK; Sema BERKTAŞ; Özlem B. SOYLU; Sedat KARADEMİR and Hüseyin ASTARCIOĞLU and Nur ARSLAN and İbrahim ASTARCIOĞLU (Turkish Journal of Gastroenterology, 2019)
-